Palm oil Sludge as Energy Substitute in Finisher Broiler Diets: A Pathway Out of the Current Feed Energy Crisis - Anyanwu, N.J.; Imoh, G.C.; Imoh, A.S.; Ekette, I.E. (Nigerian Journal of Animal Science, 2026)
The high cost of energy feed ingredients has pushed feed prices to astronomical levels thereby making cost of mature broiler chickens out of reach of the average consumer. In a bid to keep poultry producers in business the search for cheaper alternative feed ingredients would continue to ensure that consumers have access to live chickens at affordable costs. This experiment investigated the effect of different levels of inclusion of enzyme supplemented Palm Oil Sludge (POS) in the diet of finisher broiler birds. One hundred and twenty 4 week-old birds of the Ross 308 strain were randomly allotted to four treatment diets in a completely randomized design with three replications. Each treatment group contained 30 birds with 10 birds per replicate. Four diets were formulated such that palm oil sludge (POS) replaced maize at 5, 10 and 15% respectively, designated as T2, T3 and T4. The control treatment T1contained no palm oil sludge. The experiment lasted for 28 days. The results showed that the birds on T4 recorded significantly higher weight gains, better feed conversion ratio, reduced feed intake and lower feed costs when compared to the other treatments. Birds on 15% inclusion level recorded final body weight of 2.42kg compared to 2.25kg for the control treatment. It can be concluded that inclusion of enzyme supplemented Palm oil sludge at 15 % in finisher broiler diet resulted in increased weight gains and cheaper feed cost which is therefore recommended for adoption by farmers and feed millers in this era of exorbitant cost of feed and mature broiler birds.